A dual material removal mechanism for clearing of obstructed holes via electrical discharge machining. (January 2022) - Castro-Palacios, Monica; Ahmed, Shamraze; Ahmed, Nuhaize; Murray, James W.; Speidel, Alistair; Duffin, Jason; Kell, James; Clare, Adam T.
Abstract: Cooling hole blockages in gas turbine blades can occur during operation, detrimentally reducing performance and resulting in premature removal from service. Here, electrical discharge machining (EDM) is used to unblock fine holes, which have been obstructed with a mixture of both conductive and non-conductive contaminants representative of post-service condition. This work demonstrates EDM is a viable process to unblock fine holes containing material which is partially non-conductive. The mechanism results from a combination of conventional EDM discharges and mechanical spalling, resulting in a dual removal process. This method allows accurate and repeatable hole clearance in a conventional EDM hole-drilling setup.